PENGARUH PERBANDINGAN TEPUNG SAGU (Metroxylon sp.) DAN TEPUNG KACANG MERAH (Phaseolus vulgaris L.) TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK FOOD BAR - Soeparyo, Masyta K.; Rawung2, Dekie; Assa, Jan R. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2018)
The aim of this study was to obtain the physicochemical characteristics(moisture, ash, fat, protein, carbohydrate contents, and texture) and proper organoleptics on food bars of sago flour and red bean flour. The study was conducted in a completely randomized design with a five treatments, including A (10% sago flour and 90% red bean flour), B (20% sago flour and 80% red bean flour), C (30% sago flour and 70% red bean flour), D (40% sago flour and 60% red bean flour), E (50% sago flour and 50% red bean flour). The parameters analyzed were water, ash, fat, protein, carbohydrate content, texture, and organoleptic characteristics. All the proportions of the mixture of sago flour and red bean flour studiedproduced a food bar acceptable to the panelists even with a degree of preference that was not too high (neutral). The chemical composition of the food bar (20% sago flour and 80% red bean flour) produces a moisture content of 7.23%, ash content 1.93%, fat content 16.50%, protein content 13.98%, carbohydrate content 60.36%, and has a physical texture characteristic 23.78 mm/gr/second.Keywords : Foodbars, Sago Flour, Red Bean Flour